Cambridge Practice Tests for IELTS Vol. 1 - Jakeman, Vanessa and McDowell, Clare (UK Cambridge University Press, 2010)
This collection of practice tests contains four authentic IELTS papers from Cambridge ESOL, providing excellent exam practice.
Keywords: English language -- International English Language Testing System -- English language--Study and teaching--Foreign speakers -- English language--Examinations